2007
DOI: 10.1088/0268-1242/22/8/024
|View full text |Cite
|
Sign up to set email alerts
|

Femtosecond versus nanosecond laser micro-machining of InP: a nondestructive three-dimensional analysis of strain

Abstract: Abstract:Ultra-fast femtosecond laser micro-machining can lead to improved surface morphology and a reduction in the heat-affected zone. In this paper, synchrotron x ray topography (SXRT) and micro-Raman (µRS) has been used as nondestructive tools to compare the residual strain in InP substrates after femtosecond and nanosecond laser processing. 2-dimensional stain distributions with varying probing depth and cross section images across the 4 laser machined grooves were obtained. The re-crystallized poly-InP l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2008
2008
2009
2009

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 25 publications
(56 reference statements)
0
5
0
Order By: Relevance
“…We have evidenced a correlation between the place where damage takes place and the location of the maximal residual retardance around the mitigated site. Then again an extensive work that we will consider in a near future involving local analysis (micro-Raman spectrocopy for instance is well adapted [27]) associated with an accurate metrology of LIDT is needed to understand the potential mechanisms that can be involved. Also, we have developed a thermo-mechanical model of CO 2 laser interaction with fused silica with applications in the optimization of the mitigation of damage growth process.…”
Section: Resultsmentioning
confidence: 99%
“…We have evidenced a correlation between the place where damage takes place and the location of the maximal residual retardance around the mitigated site. Then again an extensive work that we will consider in a near future involving local analysis (micro-Raman spectrocopy for instance is well adapted [27]) associated with an accurate metrology of LIDT is needed to understand the potential mechanisms that can be involved. Also, we have developed a thermo-mechanical model of CO 2 laser interaction with fused silica with applications in the optimization of the mitigation of damage growth process.…”
Section: Resultsmentioning
confidence: 99%
“…The PSD data clearly indicate that in addition to the fundamental periodicity other periodicities are also present due to a large amount of microroughness in the structures and their magnitudes increase with the number of laser shots. Though we have kept the pulse energy density fixed at 125 mJ cm −2 , the periodicity would vary with increasing energy density for a fixed number of laser pulses [37][38][39][40]. The grating period will increase with energy density for a fixed number of laser shots due to increasing electron concentration and temperature [37] = 2π…”
Section: Resultsmentioning
confidence: 99%
“…Ultrashort lasers offer high intensity to drill, to modify and to process surfaces cleanly by aggressively driving multiphoton, tunnel ionization and electron-avalanche processes [9,10]. Also, nanosecond lasers are proven to have low power, throughput, threshold fluence and redundant debris and recast layer when compared with femtosecond lasers [11][12][13][14]. Studies in femtosecond laser fabrication have been reported at low power and low repetition rate (<1 kHz) [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%